Tafsir Ekologis Al-Qur’an Surah Al-Mu‘minun Ayat 18 - Munawarah Munawarah; Taufik Warman Mahfuzh; Rofi‘i Rofi‘i (Syams, 2020)
The problem of water quality and quantity is getting more of a concern from time to time. Water crisis, flooding, land subsidence, intrusion and rising sea levels are serious threats facing modern society today. The de-constructive behavior and exploitation of water resources on a large scale and irregular natural management make the ecosystem on earth unbalanced and in the end lead to disaster. The writing is a literature research using the Thematic Method (al-dirasah al-mawdu’iyyah), with an ecological interpretation approach. From the results of this study it was found that QS. Al-Mu'minun / 23: 18 requires an understanding of water resources based on positive and constructive culture towards the earth’s water reservoir.